HUBUNGAN KONSENTRASI HEMOGLOBIN DARAH DENGAN KEJADIAN INFARK MIOKARD AKUT DI RUMAH SAKIT UNIVERSITAS SUMATERA UTARA PERIODE 2018-2019 - Sugiono Namli (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
Background: Coronary Heart Disease (CHD) is the biggest cause of mortality and morbidity worldwide, and Acute Myocardial Infarction is the major form. The major cause of myocardial infarction is the mismatch of myocardial oxygen demand and supply. Decreased in hemoglobin concentration will result in decreased oxygen delivery in coronary blood flow. The objective is to know the association of hemoglobin concentration with acute myocardial infarction at Rumah Sakit Universitas Sumatera Utara within the periods of 2018–2019. Method: This research uses an analytic method with a cross-sectional design, and takes place at Rumah Sakit Universitas Sumatera Utara from March to December 2019. This research is conducted by looking at secondary data, using the medical records of inpatients with acute myocardial infarction at the cardiology department of Rumah Sakit Universitas Sumatera Utara within the periods of 2018–2019. The data is then analyzed using a computer program. Results: From research, there are 19 AMI patients, mostly at the age of 51–60. AMI patients are dominated by males. P-value of 0.864 is obtained through the Chi-Square method of bivariate analysis, which means statistically there is no correlation between hemoglobin concentration and acute myocardial infarction. Discussion: This study is in accordance with the findings of Sarnak et al., who stated that hemoglobin is an independent risk factor for CHD but is not significant when combined with other risk factors which is a limitation in this study. Conclusion: There was no association between hemoglobin values and the incidence of acute myocardial infarction.